Associations between daily movement behaviors, sleep, and affect in older adults: An ecological momentary assessment study - Jongwon Lee; Shang-Ti Chen; Vanessa Bartholomew; Krista Kicsak; Christine Pellegrini; Chih-Hsiang Yang (Bern Open Publishing, 2024)
Daily movement-based behaviors and sleep are associated with daily mental health outcomes. However, the associations in older adults remain unclear. This study aimed to determine the same-day association between sleep (duration and quality), physical activity (stepping) and sedentary behaviors (sitting and lying), and affect (positive and negative affect) among older adults using ecological momentary assessment (EMA). The data collection period was 14 consecutive days. Sleep logs collected sleep duration, while smartphone surveys collected sleep quality and momentary affects. The ActivPAL4 accelerometers computed daily sedentary and physical activity (PA) times. Affects were regressed on the sleep and movement-based behaviors using two separate mixed-effects models, controlling for demographics. Ninety older adults were included in the analysis: female (n = 56, 62%), white (n = 71, 79%) age (M = 68.16 yrs, SD = 6.47), sedentary time (M = 10.13 hrs/day, SD = 2.00), PA time (M = 1.60 hrs/day, SD = 0.65), sleep duration (M = 8.25 hrs/day, SD = 1.39), and sleep quality (M = 6.92/day, SD = 1.39). More sedentary, PA time, and better sleep quality than usual on a given day were associated with both lower negative affect (bs range = -0.18 - -0.02, ps range = .001 - .025) and higher positive affect (bs range = 0.05 - 0.14, p < .001). The longer sleep duration than usual on a given day was associated with lower negative affect (b = -0.06, p < .001). Participants with overall higher sleep quality than others experienced lower negative affect (b = -0.33, p = .025) and higher positive affect (b = 0.40, p < .001) across the study period. Our findings indicated that spending more time in any movements beyond the daily routine and better sleep quality may benefit older adults' psychological well-being by enhancing positive affect and reducing negative affect.